URANIUM-SERIES CHRONOLOGY AND ENVIRONMENTAL APPLICATIONS OF SPELEOTHEMS - Richards D.A.; Dorale J.A. (My University, 2003)
An increasing number of scientists recognize the value of speleothems1 as often extremely well-preserved archives of information about past climate, vegetation, hydrology, sea level, nuclide migration, water-rock interaction, landscape evolution, tectonics and human action. Well-constrained data are required to document past changes, reconstruct past patterns and predict future responses of the Earth system at a wide range of spatial and temporal scales. Speleothems are particularly useful in this regard because they can be found in many locations of the globe, sampled at high-resolution and reliably dated using high-precision uranium-series techniques. Speleothems are bodies of mineral material formed in caves as the result of chemical precipitation from groundwater flowing or dripping in a cave. Most speleothems are composed of calcite formed by slow degassing of CO2 from supersaturated groundwater, but aragonite and gypsum forms are also common, particularly near cave entrances where evaporative effects are important. A host of different speleothem types decorate the walls, ceilings and floors of caves, and their mineralogy and morphology is a function of fluid flow and chemistry of waters feeding a particular location as well as the ambient conditions (temperature, chemistry, light) in the air or water-filled void. Subaerial forms include the familiar stalagmites, stalactites, draperies, flowstones. Subaqueous forms include rimstone pools, “rafts,” mammillary calcite wall-coatings and “dog-tooth” spar. For an extensive review of the types of speleothem that have been observed, see Hill and Forti (1997). Speleothems are used in a multitude of ways to explore past environmental conditions, perhaps the most fundamental of which is their very presence or absence. Deposition of speleothems relies on sufficient water supply and soil CO2 to enable dissolution and transport of reactants in the vadose zone to underlying caves. In arid or glacial times, conditions may not have been favorable for speleothem formation. …